2010
DOI: 10.1159/000321581
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Navigation and APOE in Amnestic Mild Cognitive Impairment

Abstract: Background: The effect of APOE Ε4 allele (Ε4) on spatial navigation in amnestic mild cognitive impairment (aMCI) is unknown. Objective: Our purpose was to examine the characteristics of spatial navigation impairment in Ε4-positive (Ε4+) and Ε4-negative (Ε4–) aMCI subgroups. Methods: Blood samples were collected to determine the APOE genotype. A total of 34 aMCI patients were stratified into aMCI-Ε4– (n = 23) and aMCI-Ε4+ (n = 11) groups. Control (n = 28) and mild Alzheimer’s disease (AD; n = 16) groups were al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
48
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 78 publications
(48 reference statements)
4
48
0
3
Order By: Relevance
“…The study revealed that the performance of the apoE4 mice in the object recognition and Morris water maze was impaired relative to that of the apoE3 mice and that it was also impaired in the contextual but not in the cued fear conditioning response.These findings are in accordance with previous results obtained utilizing a dry version of the Morris water maze and fear conditioning test results, which were obtained using young apoE4 mice [23,30]. They also extend previous studies that revealed that adult apoE4 mice are cognitively impaired [32,34,36,37,41,42,43,44] and suggest that, like in humans, the apoE4-driven cognitive impairments begin early in life [45,46]. …”
Section: Discussionsupporting
confidence: 92%
“…The study revealed that the performance of the apoE4 mice in the object recognition and Morris water maze was impaired relative to that of the apoE3 mice and that it was also impaired in the contextual but not in the cued fear conditioning response.These findings are in accordance with previous results obtained utilizing a dry version of the Morris water maze and fear conditioning test results, which were obtained using young apoE4 mice [23,30]. They also extend previous studies that revealed that adult apoE4 mice are cognitively impaired [32,34,36,37,41,42,43,44] and suggest that, like in humans, the apoE4-driven cognitive impairments begin early in life [45,46]. …”
Section: Discussionsupporting
confidence: 92%
“…The differences in spatial navigation observed in the aMCI subgroups in relation to ApoE4 status are in agreement with results yielded in animal research [6] and with controversial results yielded in bapineuzumab or rosiglitazone clinical trials. As our method has been found helpful in the diagnosis of MCI patients [7,8] we are developing computer tests which can be used in a broader clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…The second reason is that the effect of APOE-ε4 on spatial navigation performances has not been tested yet in young adults. A deleterious effect has been repeatedly shown in older adults [25,26] and only once in 7-10 years old children [27] when navigational place learning is not fully developed [28]. However, episodic memory, which depends crucially on the hippocampus and also includes spatial components of memorized events, is improved in young adult APOE-ε4 carriers, while impaired in older adults [5,29].…”
Section: Introductionmentioning
confidence: 99%